Raman spectroscopy study of the role of dispersion and interfaces in the improvement of the mechanical properties of epoxy-TiO2 composites - María Fernández-Álvarez; Alberto Moure; Luis Angulo Delgado; Julián J. Reinosa; José F. Fernández (Journal of Materials Research and Technology)
The final properties and durability of advanced epoxy-based composites reinforced with ceramic particles depend on both the particle dispersion and the particle-matrix interaction. The main objective of this work is to understand the role of TiO2 particle dispersion in an epoxy matrix by high-resolution confocal Raman spectroscopy, evaluating the nature of their interaction and the crosslinking state of the polymeric matrix. These factors determine the mechanical and wear behaviour of the composites, allowing the properties of the final composite to be explained through spectroscopic measurements, depending on the dispersion state of the filler. To achieve these goals, a novel dispersion method, involving three steps (high-speed stirring, high-shear mixing, and tri-cylinder rolling), was developed. Materials composed of an epoxy matrix and submicrometric TiO2 particles (0.1–10 wt%) were manufactured using this method and a conventional mechanical agitation method commonly used for comparison. Raman spectroscopy revealed that the advanced method achieved a high degree of homogeneity, reducing filler agglomeration and improving epoxy crosslinking. The epoxy-based composites with effectively dispersed particles exhibit improved mechanical properties, such as increased hardness and reduced wear, compared to both non-reinforced epoxy and materials obtained by conventional mixing. This work highlights the importance of engineering the dispersion and interface of TiO2 particles in an epoxy matrix and demonstrates the potential to predict the final properties of a composite through a novel evaluation using Confocal Raman microscopy.